Guilty men - Foot, Michael; Owen, Frank; Howard, Peter (London : Victor Gollancz, 1940)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Wereldoorlog 2; politieke geschiedenis; Groot-Brittannië.